Q Vectors, Bicistronic Retroviral Vectors for Gene Transfer. (April 2000) - Julius, Martin A.; Yan, Qingyou; Zheng, Zhili; Kitajewski, Jan
We have developed a retroviral vector that incorporates unique features of some previously described vectors. This vector includes: 3′ long terminal repeats (LTRs) of the self-inactivating class; a 5′ LTR that is a hybrid of the cytomegalovirus (CMV) enhancer and the mouse sarcoma virus promoter; an internal CMV immediate early region promoter to drive expression of the transduced gene and the neomycin phosphotransferase selectable marker; an expanded multiple cloning site and an internal ribosome entry site. An SV40 ori was introduced into the vector backbone to promote high copy number replication in packaging cell lines that express the SV40 large T antigen. We demonstrate that these retroviral constructs, designated Q vectors, can be used in applications where high viral titers and high level stable or transient gene expression are desirable.